2017
DOI: 10.21767/2573-0282.100038
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Signalling that Associated with Influenza A Virus Infection

Abstract: Influenza-A virus infection induces a variety of intracellular signalling pathways that are either antiviral or required to ensure efficient replication. A prominent cellular antiviral event is the activation of cascade that produces type I interferon's (IFNs): IFN-α and IFN-β. Consequently, an appreciated number of antiviral proteins that encoded by so-called IFN stimulated genes are activated, such as Mx1, PKR and ISG-15 genes. Conversely, virus-supportive signalling processes activated upon infection are I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The MAPK pathway is required to control many cellular processes, including cell differentiation, cell division, cell proliferation, programmed cell death, and inflammation. MAPK/ERK signaling pathway includes activation of Raf protein kinase, MEK1/2, and the transcription factor ERK1/2 (29, 30). This pathway is activated in cancer cells due to the activation of mutant K-Ras and mutant B-Raf proteins which responsible for the limitation of programmed cell death and for raising the production level of TGF-β and IL-8 (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway is required to control many cellular processes, including cell differentiation, cell division, cell proliferation, programmed cell death, and inflammation. MAPK/ERK signaling pathway includes activation of Raf protein kinase, MEK1/2, and the transcription factor ERK1/2 (29, 30). This pathway is activated in cancer cells due to the activation of mutant K-Ras and mutant B-Raf proteins which responsible for the limitation of programmed cell death and for raising the production level of TGF-β and IL-8 (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PI3K and its downstream targets Gbr2, pip3, PDK and Akt protein kinase has been detected at early stages upon influenza infection (5‐9 hours post infection) . The PI3K‐Akt pathway is known to play an antiapoptotic role; therefore the activation of the PI3K/Akt pathway limits virus‐induced cell death or apoptosis in infected cells (Figure ). Conversely, at late stages of infection (17‐20 hours after infection), the P13K‐Akt pathway is inactivated due to the activation of pro‐apoptotic p53 signaling and its related targets p21/waf .…”
Section: Discussionmentioning
confidence: 99%
“…Blocking of PI3K-Akt signaling by GFGs enables the activation of P53 and its related cytokines that control cell survival and virus replication. GFGs, guava flavonoid glycosides; IAV, influenza A virus activation of the PI3K/Akt pathway limits virus-induced cell death or apoptosis in infected cells 26,40,41 (Figure 6). Conversely, at late stages of infection (17-20 hours after infection), the P13K-Akt pathway is inactivated due to the activation of pro-apoptotic p53 signaling and its related targets p21/waf.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in order to identify unknown methylation hot-spots or methylated CpG islands in the genome, several of genome-wide screen methods have been invented such as Restriction Landmark Genomic Scanning for Methylation (RLGS-M), and CpG island microarray. Several studies have implicated the biological role and molecular interaction of DNMTs in cancer, aging and hepatitis C virus infection [8]. The expression of DNMT1 is increased in cancer and induces DNA methylation of various tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autophagy has been shown to play an important role in cell growth, development and disease pathology [7]. Notably, several studies indicated the essential role of autophagic machinery in regulating viral infection [8]. Activation of autophagy machinery is one of the down-stream events of a class III phosphatidylinositl I 3-kinase (PI 3-K) complex.…”
Section: Introductionmentioning
confidence: 99%